Patch three-dimensional effect for plant species diversity of urban remnant mountain in multi-mountain city. (July 2022) - Zeng, Mulin; Bao, Yu; Wang, Zhitai; Huang, Zongsheng; Chen, Xintong; Wei, Wenfei; Lin, Xun; Li, Qin
Highlights: The patch characteristics of urban remnant mountains (URMs) were more complex than those of general remnant habitats. Generally, the morphological characteristics of URMs had a more significant effect on plant diversity at herb level. The plant diversity of tree level at the mountainside was more responsive to the surface morphological indicators. URMs morphological characteristics had the most significant effect on α and β diversity of plant species on the southern slope. URMs morphological characteristics were able to influence the plant diversity among and within URMs, but to explain the diversity gradient poorly. Abstract: In some karst mountainous areas, with the urban expansion driven by rapid urbanization, a large number of natural mountains that were not suitable for development and construction were embedded into the urban built environment, forming urban remnant mountains(URMs). In this study, we conducted a indicator system to explore the relationship between morphological characteristics of URM and its plant species diversity. The results showed that: (i) The two boundary plane morphological indicators of URMs were significantly associated with its plant species α and β diversity; among the overall morphological indicators, mountain form factor ( MFF ) was significantly associated with plant species α and β diversity, mountain size coefficient ( MSC ) was negatively related to Margalef ( R ) index, and mountain volume density ( MVD ) had no significant relationship with plant diversity. Additionally, surface morphological indicators were significantly negatively correlated with the Pielou ( Jgi ) index, and positively correlated with Jaccard ( Cj ) and Sorenson ( Cs ) indices. (ii) There were also differences in the influence of morphological characteristic indicators of URMs on the plant species diversity of its different slope position and slope direction. Mountain shape index ( MSI ), mountain fractal dimension ( MFD ) and MFF had significant influence on plant species α and β diversity indices of different slope position and slope direction; All surface indicators of URMs morphological characteristics were significantly associated with plant species α and β diversity indices on the southern slope of URMs. (iii) The effects of URMs morphological indicators on plant diversity of different life forms were different, and the influence of herb plant diversity was more significant. (iiii) The multiple regression analysis showed that the URM morphological characteristic indicators could explain the difference of plant species α diversity among different URMs, while the interpretation of plant species β diversity among URMs was poor. In general, the three-dimensional characteristics of the URM are complex and particularity, and the quantitative indicators of different dimensions all showed the impact on the plant species diversity of the URMs. This study demonstrated that the ecological processes of the URM habitats have more complex patch effects in response to interference as compared to the general remnant habitat.